Bridging the Gap: Improving Acute Ischemic Stroke Outcomes with Intravenous Thrombolysis Prior to Mechanical Thrombectomy - Jessica Seetge; Balázs Cséke; Zsófia Nozomi Karádi; Edit Bosnyák; László Szapáry (Neurology International)
Background/Objectives: Current guidelines recommend intravenous thrombolysis (IVT) followed by mechanical thrombectomy (MT) for patients with acute ischemic stroke (AIS) caused by large vessel occlusion (LVO). This combined approach, known as bridging therapy (BT), is believed to increase the likelihood of a favorable functional outcome when administered within 4.5 h of symptom onset. However, the benefits of BT over direct mechanical thrombectomy (d-MT) remain debated. This study aimed to compare the outcomes of AIS-LVO patients undergoing MT within 6 h of symptom onset, with and without prior IVT. Methods: Within the prospective Transzlációs Idegtudományi Nemzeti Laboratórium (TINL) STROKE-registry, AIS-LVO patients admitted to the Department of Neurology, University of Pécs between February 2023 and June 2024 were investigated. The primary endpoint was the proportion of patients reaching functional independence at 90 days, defined as a modified Rankin Scale (mRS) score of 0–2. Secondary endpoints included clinical improvement at 72 h (National Institute of Health Stroke Scale [NIHSS] score of ≤1 or a change from baseline [ΔNIHSS] of ≥4) and successful recanalization (modified Thrombolysis in Cerebral Infarction [mTICI] score ≥ 2). Safety outcomes were evaluated based on thrombus migration and intracranial hemorrhage (ICH). Results were compared using linear and logistic regression analyses adjusted for baseline variables. Results: Of 82 patients, 51 (62.2%) received BT, while 31 (37.8%) underwent d-MT. The BT group showed a significantly higher rate of functional independence (45.7% vs. 17.2%, p = 0.014) and a lower 90-day mortality rate (13.7% vs. 35.5%, p = 0.029). Multivariate analysis revealed that IVT was independently associated with favorable functional outcomes (p = 0.011) and reduced mortality (p = 0.021). No significant differences were observed in terms of clinical improvement at 72 h, successful recanalization, thrombus migration, or hemorrhagic transformation between the groups. Conclusions: This study supports current guidelines recommending BT for thrombectomy-eligible AIS-LVO patients, offering new insights into the ongoing clinical debate.